Analysis Of The Application Of Occupational Safety and Health (K3) Management To Radiation At The Radiology Installation Of Ernaldi Bahar Hospital, South Sumatra Province - Rizki Dien Wahyuni; Desheila Andarini; Anita Amelia; Imelda G. Purba; Dwi Septiawati (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Introduction: The radiation dose is not controlled then the dose value will be accumulated. Then the dose received will be higher so that it can cause a drastic reduction in the number of lymphocytes. The purpose of this study was to analyze the application of occupational safety and health (K3) management to radiation at the radiology installation of Ernaldi Bahar Hospital, South Sumatra Province. Methods: This study uses qualitative methods with observational approaches, interviews and document studies. Result: The application of radiation safety management requirements at the radiology installation of Ernaldi Bahar Hospital, South Sumatra Province has not been carried out optimally. The application of radiation protection requirements, application of technical requirements, application of safety verification and health monitoring of radiation workers have been carried out properly. Conclusion: The implementation of occupational health and safety management on radiation at the radiology installation of Ernaldi Bahar Hospital, South Sumatra Province, has been going well. Keywords: Radiation, Management to Radiation, X-ray